Ethical behaviour among registered and non-registered counsellors - Mat Rani, Nurul Hasyimah; Wan Jaafar, Wan Marzuki; Mohd Noah, Sidek (Institute of Advanced Science Extension (IASE), 2017)
This study seeks to identify whether or not there is a difference in the ethical behaviour of registered counsellors and non-registered counsellors. This study also seeks to identify if there is a difference between ethical behaviour based on the demographic factors of age, gender, experience and qualification of the counsellors. The study design adopted is the ex-post facto design. The study sample comprises of 355 registered counsellors and non-registered counsellors all over Malaysia. The study tool employed is Ethics Practice Survey adapted by previous research. The analyses used are the T-test and the One-Way ANOVA. The study results show that registered counsellors have more ethics if compared to their non-registered counterparts. Next, the study results also demonstrate that there is a significant difference between the ethical behaviour of counsellors according to their age, gender, experience and qualification of counsellors. The implications of the study are also elaborated.